Medical Record Information System with Rapid Application Development (RAD) Method - Pratiwi, Mutiana; Mayola, Liga; Kris Hiburan Laoli, Vince; Ilhami Arsyah, Ulya; Pratiwi, Nila (Journal of Information Systems and Technology Research, 2022)
Computer technology that is increasingly developing has created a situation that demands everything to be computerized. Science from technology has also changed the way of life of most Indonesians. The presence of information and communication technology affects the technology applied in information systems, especially the input and output mechanisms. One of them is at the Clinic which requires computer technology in its operations. The design of this website also uses 3 stages of Rapid Application Development (RAD) system design, the result of which is a website for a medical record information system. In order for clinical activities to run smoothly at the Clinic, an information system using the Rapid Application Development (RAD) method is needed because the software development process model is classified as an incremental technique and emphasizes short, short, and fast development cycles. Medical record system testing will be tested using Blackbox Testing and User Acceptance Test (UAT) testing.